Comparison of Ultrasound-Guided Erector Spinae Plane Block and Oblique Subcostal Transversus Abdominis Plane Block in Post-Operative Pain Management for Laparoscopic Cholecystectomy Patients - Rahma Lodi, Kenza Ahsan, Roomi Ahmer, Sarah Nadia Jamal, Zaigham Din Baloch, Kiran Qamar (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Laparoscopic cholecystectomy is a frequently performed minimally invasive surgery associated with significant postoperative pain, which can delay recovery and increase opioid use. Regional anesthesia techniques such as the erector spinae plane (ESP) block and oblique subcostal transversus abdominis plane (OSTAP) block have been utilized to improve postoperative analgesia, but comparative data on their efficacy remain limited. Objectives: To compare the analgesic efficacy of ultrasound-guided ESP block and OSTAP block in managing postoperative pain following laparoscopic cholecystectomy. Study Design & Setting: This was a prospective, randomized, controlled study conducted at Department of Anaesthesia and Intensive Care NICVD from January 2023 to June 2023 involving 120 patients scheduled for elective laparoscopic cholecystectomy. Methodology: Patients aged 18–65 years with ASA physical status I or II were randomly assigned to receive either ESP block (Group A) or OSTAP block (Group B) preoperatively. Both groups received 20 ml of 0.25% bupivacaine under ultrasound guidance. Postoperative pain was assessed using the Visual Analog Scale (VAS) at rest and during coughing at 1, 4, 8, 12, and 24 hours. Secondary outcomes included total opioid consumption in 24 hours, incidence of side effects, and patient satisfaction. Results: Group A demonstrated significantly lower VAS pain scores at all time points both at rest and during coughing (p < 0.005). Total opioid consumption was also significantly reduced in Group A (8.7 ± 2.5 mg) compared to Group B (12.1 ± 3.4 mg) (p < 0.001). Side effects were comparable between groups without statistically significant differences. Clinical Implication: The ESP block offers superior postoperative analgesia and opioid-sparing benefits, potentially improving recovery quality in laparoscopic cholecystectomy patients. Conclusion: Ultrasound-guided ESP block is more effective than OSTAP block in reducing postoperative pain and opioid use, making it a preferable analgesic technique in laparoscopic cholecystectomy. Keywords: Erector spinae plane block, laparoscopic cholecystectomy, opioid consumption, postoperative pain, transversus abdominis plane block